Method for forming a low carbon contamination silicon single crystalline ingle and
By depositing a coating of boron nitride and sintering additives on the inner surface of the graphite crystal holder, a chemical inert barrier was formed, which solved the problem of carbon pollution between graphite and quartz during the Chuklasky process, and improved the quality and crystalline of the silicon ingot The lifespan of the seat.
Patent Information
- Application Number
- CN202380043877.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-05-30
- Publication Date
- 2025-01-10
AI Technical Summary
During the Chuklasky process, the reaction between the graphite crystal holder and the quartz crucible leads to carbon pollution, affecting the quality of the silicon crystal and the service life of the crystal holder. The prior art is difficult to effectively reduce carbon pollution and prevent cross-contamination.
The coating of boron nitride and sintering additives is deposited on the inner surface of the graphite crystal base to form a chemical inert barrier, inhibit the reaction between graphite and quartz, and promote the densification of boron nitride through the sintering additives to reduce carbon cross-contamination.
It effectively reduces the carbon content in the silicon crystal, extends the service life of the crystal holder, and increases the resistivity of the silicon ingot, reducing the impact of carbon pollution on the performance of semiconductor devices.
Smart Images

Figure CN119301314A_ABST
Abstract
Description
[0001] CROSS REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 347,897, filed on June 1, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The field of the present disclosure relates to methods of forming low carbon contamination single crystal silicon ingots in a Czochralski process. In embodiments disclosed herein, a protective coating is used to reduce or prevent reaction between a graphite crystal susceptor and a quartz crucible used during the process. In some embodiments, the coating comprises boron nitride and a sintering additive that promotes densification of the boron nitride to help prevent or minimize cross contamination of the silicon ingot with boron and / or nitrogen. Background Art
[0004] Single crystal silicon is the starting material for most processes used to make many electronic components such as semiconductor devices and solar cells, and is often prepared by a batch Czochralski (CZ) process or a continuous Czochralski (CCZ) process. In these processes, polycrystalline raw materials (e.g., polycrystalline silicon (polycrystalline silicon or polysilicon)) in the form of solid feedstock material are charged into a quartz crucible and melted, a single seed crystal is brought into contact with the molten silicon or melt, and a single crystal silicon ingot is grown by slow extraction.
[0005] Polycrystalline silicon can also be directly cast into ingots using a directional solidification process. Wafers cut from polycrystalline silicon ingots are often used in the electronics industry and in photovoltaic cells for the production of solar energy. In general, polycrystalline silicon is the preferred silicon source for photovoltaic cells, rather than single crystal silicon, because compared with typical single crystal silicon production, polycrystalline silicon is cheaper due to higher flux rates, less labor-intensive operations, and less supply costs. In the directional solidification process, raw silicon is melted in a quartz crucible and directionally solidified in a separate crucible or in the same crucible. The solidification of the ingot is controlled so that the molten silicon solidifies unidirectionally at the solidification front of the casting. The polycrystalline silicon produced in this way is an agglomeration of crystal particles, and the orientation of the particles is random relative to each other due to the high density of heterogeneous nucleation sites at the crucible wall. Once the polycrystalline silicon ingot is formed, the ingot can be cut into blocks, and further cut into wafers.
[0006] In these methods, the quartz crucible is not dimensionally stable at the high temperatures required to melt the solid feedstock material. To prevent warping or deformation of the crucible during the crystal growth process, the crucible is supported by a crystal susceptor suitably formed of a carbonaceous material such as graphite. Graphite is dimensionally stable at the temperatures required to melt the silicon feedstock material.
[0007] During the crystal growth process, carbon from the graphite crystal base and silicon dioxide from the quartz crucible may react with each other to produce carbon oxide products and silicon oxide products in gaseous form, for example, by the following reaction:
[0008] SiO2+C→SiO(g)+CO(g); and
[0009] SiO2+3C→SiC+2CO(g).
[0010] These and other gaseous products (e.g., CO2) are carried away by the inert gas flowing around the susceptor and crucible, and may be swept into the silicon melt, thereby contaminating the melt with carbon. As the inert gas flow carries away the gaseous reaction products, new carbon and silicon dioxide surfaces are exposed, thereby promoting continued reactions between the crucible and susceptor, and causing further contamination of the melt. Silicon ingots grown from the melt and wafers cut from these ingots may have relatively high carbon concentrations.
[0011] It is well known that carbon contamination can cause current leakage in semiconductor devices and thus result in poor performance of the semiconductor devices. Therefore, it is desirable to minimize carbon contamination of the melt and eliminate potential carbon sources during the CZ and CCZ crystal growth process.
[0012] The continuous reaction between the crucible and the reactor also causes erosion of the crucible and the crystal susceptor. Typically, the crucible is used for a single growth process, while the crystal susceptor can be used for multiple runs. However, due to the continuous cycle of erosion of the crystal susceptor, the crystal susceptor deteriorates rapidly, which shortens the service life of the crystal susceptor. Therefore, in both the CZ and CCZ crystal growth processes and the directional solidification process, it is desirable to minimize the reaction between the crucible and the crystal susceptor to provide a longer-lasting crystal susceptor.
[0013] Well-known systems and methods for attempting to address and / or reduce carbon contamination of the melt during the crystal growth process are insufficient to meet current and future carbon requirements for advanced semiconductor devices and / or to prevent cross contamination of the silicon crystal with materials used to prevent reactions between the crucible and the susceptor.
[0014] There is a need for a method for preparing a silicon ingot that helps reduce the carbon content in the silicon crystal and helps prevent cross contamination of the silicon crystal with inert coating materials.
[0015] This section is intended to introduce the reader to various aspects of the technology that may be related to the various aspects of the present disclosure that will be described and / or claimed below. It is believed that this discussion is helpful in providing the reader with background information to facilitate a better understanding of the various aspects of the present disclosure. Therefore, it should be understood that these descriptions should be read in this light, and not as an admission of background technology. Summary of the invention
[0016] In one aspect, a method for producing a single crystal silicon ingot from a silicon melt includes providing a graphite crystal seat having an inner surface defining a cavity and depositing a coating onto the inner surface of the crystal seat. The coating includes boron nitride and a sintering additive. The sintering additive promotes densification of the boron nitride. The method also includes positioning a quartz crucible in the cavity of the crystal seat. The crucible has an outer surface that contacts the coating. The method further includes adding polycrystalline silicon to the crucible, heating the polycrystalline silicon to cause a silicon melt to form in the crucible, and pulling a single crystal silicon ingot from the silicon melt.
[0017] In another aspect, a graphite crystal holder for supporting a quartz crucible during a crystal growth process comprises a body having an inner surface and a coating deposited onto the inner surface. The inner surface defines a cavity. The cavity has a size and shape complementary to an outer size and shape of the crucible. The coating comprises boron nitride and a sintering additive. The sintering additive is configured to promote densification of the boron nitride.
[0018] In another aspect, a method for forming a coating between an inner surface of a graphite crystal base and an outer surface of a quartz crucible comprises providing a particulate mixture of boron nitride and a sintering additive, depositing the particulate mixture of the boron nitride and the sintering additive onto the inner surface of the crystal base, and sintering the deposited particulate mixture to thereby form the coating. Sintering the deposited particulate mixture comprises using the sintering additive to promote densification of the boron nitride.
[0019] There are various refinements of the features noted with respect to the above-mentioned aspects. Other features may also be incorporated into the above-mentioned aspects of the present disclosure. These refinements and additional features may exist individually or in any combination. For example, various features discussed below in connection with any of the illustrated embodiments may be incorporated into any of the above-described aspects of the present disclosure individually or in any combination. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a schematic cross-sectional side view of a pulling apparatus for forming a single crystal silicon ingot;
[0021] Figure 2 is used for Figure 1 An exploded cross-sectional view of a crucible and a crystal holder in a pulling apparatus shown in , the crystal holder having a protective coating according to an embodiment of the present disclosure; and
[0022] Figure 3A and 3B It is used to prepare Figure 2 Schematic illustration of a particulate mixture of an inert material and a sintering additive for a protective coating shown in FIG.
[0023] Corresponding reference characters indicate corresponding parts throughout the drawings. DETAILED DESCRIPTION
[0024] refer to Figure 1 , an ingot pulling apparatus or ingot puller is schematically illustrated and generally indicated as 100. The ingot puller 100 is used to produce single crystal (i.e., single crystal) ingots of semiconductor or solar grade materials, such as single crystal silicon ingots. In some embodiments, the ingots are grown by a so-called Czochralski (CZ) process, in which the ingots are extracted from a silicon melt 102 contained in a crucible 104 of the crystal puller 100. In some embodiments, the ingots are grown by a batch CZ process, in which an amount of polycrystalline silicon sufficient to grow one ingot is charged into the crucible 104, such that the crucible 104 is substantially depleted of the silicon melt 102 after one ingot is grown. In other embodiments, the ingots are grown by a continuous CZ (CCZ) process, in which polycrystalline silicon is continuously or periodically added to the crucible 104 to replenish the silicon melt 102 during the growth process. The CCZ process facilitates the growth of multiple ingots pulled from a single melt 102. However, embodiments of the subject matter described herein are not limited to a particular crystal growth process. For example, in other embodiments, a directional solidification process for a solar application process may be used to grow a multicrystalline silicon ingot.
[0025] The ingot puller 100 includes a housing 106 defining a crystal growth chamber 108 and a pulling chamber 110 having a smaller lateral dimension than the growth chamber 108. The growth chamber 108 has a generally dome-shaped upper wall 112 that transitions from the growth chamber 108 to the narrowed pulling chamber 110. The ingot puller 100 includes an inlet port 114 and an outlet port 116 that can be used to introduce process gases into and remove them from the ingot puller 100 during crystal growth.
[0026] A crucible 104 within the ingot puller 100 contains a silicon melt 102 from which a silicon ingot is extracted. The crucible 104 may be made of quartz or fused silicon dioxide, which has a high melting point and high thermal stability and is substantially non-reactive with the molten silicon in the melt 102. It should be understood that the crucible 104 may be made of other materials besides quartz without departing from the scope of the present disclosure. For example, the quartz crucible 104 may be made of a composite material including silicon dioxide and additional materials such as silicon nitride or silicon carbide.
[0027] The silicon melt 102 is obtained by melting polycrystalline silicon that is charged into the crucible 104. In a continuous system, a feed system (not shown) is used to deliver solid feedstock material to the crucible assembly 104 and / or the melt 102. The crucible 104 is positioned within and supported by a susceptor 118, which in turn is supported by a rotatable shaft 120. The susceptor 118 and rotatable shaft 120 facilitate rotation of the crucible 104 about the central longitudinal axis X of the ingot puller 100.
[0028] A heating system 122 (e.g., one or more resistive heaters) surrounds the susceptor 118 and crucible 104 and supplies heat via conduction through the susceptor 118 and crucible 104 to melt the silicon charge to produce the melt 102 and / or maintain the melt 102 in a molten state. The heater 122 may also extend below the susceptor 118 and crucible 104. The heating system 122 is controlled by a control system (not shown) so that the temperature of the melt 102 is precisely controlled throughout the pulling process. For example, the controller may control the current provided to the heating system 122 to control the amount of thermal energy supplied by the heating system 122. The controller may control the heating system 122 so that the temperature of the melt 102 is maintained above approximately the melting temperature of silicon (e.g., approximately 1412° C.). For example, the melt 102 may be heated to a temperature of at least approximately 1425° C., at least approximately 1450° C., or even at least approximately 1500° C. Insulation material (not shown) surrounding the heating system 122 can reduce heat lost through the housing 106. The ingot puller 100 can also include a heat shield assembly (not shown) above the surface of the melt 102 for shielding the ingot from the heat of the crucible 104 to increase the axial temperature gradient at the solid-melt interface.
[0029] A pulling mechanism (not shown) is attached to a pulling wire 124 extending downwardly from the mechanism. The mechanism is capable of raising and lowering the pulling wire 124 as well as rotating the pulling wire 124. Depending on the type of puller, the ingot puller 100 may have a pulling shaft instead of a wire. The pulling wire 124 terminates in a pulling assembly 126 that includes a crystal chuck 128 that holds a seed crystal 130 for growing a silicon ingot. As the ingot grows, the pulling mechanism lowers the seed crystal 130 until it contacts the surface of the silicon melt 102. Once the seed crystal 130 begins to melt, the pulling mechanism slowly raises the seed crystal through the growth chamber 108 and the pulling chamber 110 to grow a single crystal ingot. The speed at which the pulling mechanism rotates the seed crystal 130 and the speed at which the pulling mechanism raises the seed crystal (i.e., the pulling rate v) are controlled by a control system. As the seed crystal 130 is slowly raised from the melt 102 , silicon atoms from the melt 102 align themselves with the seed crystal 130 and attach to the seed crystal to form an ingot.
[0030] Process gas (eg, argon) is introduced into the growth chamber 108 and the pulling chamber 110 through the inlet port 114 and extracted through the outlet port 116. The process gas forms atmospheric pressure within the housing and the melt forms a melt-gas interface with the atmospheric pressure. The outlet port 116 is in fluid communication with the exhaust system of the ingot puller (not shown).
[0031] During operation, the temperatures required to melt the silicon charge and / or maintain the melt 102 may also cause the quartz crucible 104 to soften. The susceptor 118, which may be made of graphite or other graphene-containing or carbon-containing materials having high thermal stability, provides a rigid outer structure for supporting the softened crucible 104. At the pulling process temperature, the contact between the crucible 104 and the susceptor 118 may enable silicon dioxide from the quartz crucible 104 to react with carbon from the susceptor 118. The reaction causes the silicon dioxide to decompose into silicon oxide (SiO) gas and causes the carbon to oxidize to form gaseous carbon-containing reaction products (e.g., carbon monoxide (CO) and carbon dioxide (CO2)). As a result, the graphite susceptor 118 may be eroded, which may form voids or cavities in the susceptor 118. Structural degradation caused by such erosion may shorten the useful life of the susceptor 118 and may require replacement of the susceptor 118. Additionally, the process gas flowing through the ingot puller 100 may carry gaseous carbon-containing reaction products away from the crucible 104 and the crystal susceptor 118 and into the melt 102. This exposes fresh carbon and silicon dioxide surfaces, resulting in continued formation of gaseous carbon-containing reaction products and erosion of the crystal susceptor 118. Carbon species carried into the melt 102 may travel to the solid-melt interface of the growing ingot by countercurrent flow. As a result, the ingot pulled from the melt 102 may be contaminated with carbon. Carbon contamination of the ingot may cause wafers cut from the ingot to have poor performance in an end-use structure or device.
[0032] Reference now Figure 2 , shows an exploded cross-sectional view of a crystal holder 118 and a crucible 104. The crystal holder 118 includes a body 132 including an inner surface 134 defining a cavity 136 sized to receive the quartz crucible 104. When the crucible 104 is positioned within the cavity 136, the crucible 104 has an outer surface 138 oriented toward the inner surface 134 of the crystal holder 118. The outer surface 138 of the crucible 104 has a shape corresponding to the shape of the cavity 136 defined by the inner surface 134 of the crystal holder 118, so that the crucible 104 fits into and is supported by the inner surface 134 of the crystal holder 118 during the pulling process.
[0033] The inner surface 134 of the crystal pedestal 118 is coated with a protective coating 140. The coating 140 may completely cover or substantially cover the inner surface 134, or may cover at least a portion of the inner surface 134. During ingot growth, the crucible 104 contacts the coating 140. The coating 140 suitably covers a sufficient portion of the inner surface 134 to inhibit or prevent contact between the outer surface 138 of the quartz crucible 104 and the inner surface of the graphite crystal pedestal 118. In some embodiments, the coating 140 may additionally or alternatively cover areas other than the inner surface 134 so that the coating 140 can inhibit or prevent contact between the graphite crystal pedestal 118 and the quartz crucible 104 and otherwise function as described herein. For example, in addition to or instead of covering the inner surface 134 of the crystal pedestal 118, the coating 140 may cover at least a portion of the outer surface 138 of the crucible 104.
[0034] The coating 140 is suitably formed of a material that is chemically inert to both the carbon of the crystal susceptor 118 and the silicon dioxide of the crucible 104 under the pulling process conditions (e.g., at the pulling temperature). In this regard, the coating 140 provides a chemically inert barrier that limits, inhibits, or prevents direct contact between the graphite crystal susceptor 118 and the quartz crucible 104, and limits, inhibits, or prevents reaction between the carbon of the crystal susceptor 118 and the silicon dioxide of the crucible 104 under the processing conditions generated within the ingot puller 100.
[0035] The inert material used to form the coating 140 may be boron nitride (BN), silicon nitride (Si3N4), or a combination thereof. Boron nitride may be particularly suitable as an inert material because it has high thermal and chemical stability and is resistant to oxidation even at high temperatures. During the drawing process, silicon nitride may tend to form Si-ON compounds using various stoichiometries at high temperatures. As the temperature increases (e.g., above 1550° C.), the Si-ON bonds may tend to sublimate into other gas phases that degrade the coating 140. Boron nitride (BN) does not have a similar tendency to form oxidation products due to the strength of the covalent bonds between the boron atoms and the nitrogen atoms, and may have a higher upper functional temperature limit than silicon nitride.
[0036] The coating 140 may be applied as a coating composition comprising particles of an inert material suspended in a liquid solution. Suitably, when the coating composition is applied to the inner surface 134 of the crystal seat 118, the coating composition comprises particles of an inert material (e.g., boron nitride) suspended in a liquid solution in an amount that facilitates sufficient overlap between the particles of the inert material. For example, the coating composition may comprise at least about 5% by weight of particles of the inert material. In some embodiments, the coating composition comprises at least about 15% by weight, or even at least about 30% by weight of particles of the inert material. In various embodiments, the coating composition may comprise from about 5% to about 50% by weight of particles of the inert material, from about 15% to about 50% by weight, from about 10% to about 40% by weight, from about 20% to about 40% by weight, or from about 30% to about 40% by weight of particles of the inert material. In some embodiments, the coating composition comprises about 37.5% by weight of particles of the inert material. In some embodiments, the coating composition comprises approximately 25% inert material particles by weight. For the purposes of this disclosure, and unless otherwise specifically described, the percentages of the components included in the "coating composition" or simply "composition" refer to the material initially applied to the inner surface 134 of the crystal base 118 (e.g., inert material particles suspended in a liquid solution), rather than the coating 140 itself formed after additional processing steps (e.g., medium vaporization, heating or sintering, etc.). Unless otherwise specifically described, the percentage (%) of a component by weight means the amount of the component in the composition based on the total weight of the composition.
[0037] Without being bound by a particular theory, it is believed that the size of the inert material particles can affect the rheology of the coating composition and affect the ease of application. In some embodiments, the average nominal diameter of the inert material particles can be less than about 100 μm. In other embodiments, the average nominal diameter of the inert material particles can be less than about 50 μm, less than about 25 μm, or even less than about 10 μm. Utilizing a smaller particle size generally results in a coating composition having improved flowability. When the inert material particles are boron nitride, the boron nitride particles have a d 50 (median value) is about 0.5um and d 90 The inert material particles may also be described as a powder, or as nano-sized particles.
[0038] When applied as a liquid solution with suspended particles of inert material, the coating composition comprises additional components such as media, binders, dispersants, stabilizers, etc. The components are selected so that the formulation does not devitrify quartz or SiO. The components contemplated for use in the coating composition will now be described.
[0039] The composition may include a medium in which the inert material (e.g., boron nitride) remains substantially in particulate form. In general, it is understood that one or more of the inert material and additives (e.g., binders, dispersants, stabilizers, etc.) may not dissolve, partially dissolve, or completely dissolve in the medium, and the terms "medium," "diluent," and "solvent" may be used interchangeably and are not intended to limit embodiments of the present disclosure to compositions in which one or more components may or may not dissolve in the medium.
[0040] The medium may comprise an organic compound or may be aqueous. However, it should be noted that the presence of water in an aqueous solution may result in more oxygen in the cured coating that may react with the graphite crystal base 118 at higher processing temperatures. Therefore, while aqueous solutions may be utilized without departing from the present disclosure, the use of a non-aqueous medium may be preferred in some embodiments. Preferably, the medium is easily vaporized during any drying step. In instances where an aqueous medium is used for the liquid solution, the composition may be adjusted according to the amount of additional components present (e.g., binders, dispersants, and / or stabilizers described further below) so as to achieve a desired liquid viscosity of the liquid coating composition.
[0041] The medium may include C1 to C10 ethanol and may be isopropanol or ethanol. The amount of medium is selected to obtain the appropriate liquid viscosity of the liquid coating composition. In some embodiments, the coating composition includes at least about 10% medium by weight. In other embodiments, the composition may include at least about 30%, at least about 50%, or even at least about 70% medium by weight. In various other embodiments, the composition includes from about 10% to about 80% medium by weight, from about 30% to about 70%, from about 40% to about 60%, or even from about 45% to about 55% medium by weight. In some embodiments, the composition may include about 49.5% medium by weight. The composition may include more than one medium, wherein the total weight fraction of the medium in the composition is as described above. It should be understood that the composition may include other medium amounts in order to obtain the appropriate liquid viscosity of the liquid coating composition. The amount of medium may vary depending on, for example, the type of medium used (e.g., organic or aqueous). In addition, the appropriate liquid viscosity of the liquid coating composition may vary depending on the technology used to apply the liquid coating composition. For example, as described below, aerosol spray techniques may require a lower liquid viscosity of the liquid coating composition than brushing techniques.
[0042] The coating composition may also include one or more binders that serve to bond the components of the composition (and more particularly, the inert material (e.g., boron nitride) particles) to the inner surface 134 of the crystal base 118 and to each other after application. In general, the binder modifies the rheology of the coating composition and maintains the particle distribution in the medium throughout application and drying. In some embodiments, the binder is soluble in the medium. In some embodiments, the binder is polyvinyl butyral, such as B-76 (available from Eastman). In some embodiments, the coating composition comprises at least about 0.5%, at least about 2%, at least about 5%, or at least about 10%, or even at least about 15% binder by weight. In various embodiments, the composition comprises from about 0.5% to about 20% binder by weight, from about 0.5% to about 10%, from about 0.5% to about 8%, or from about 2% to about 8% binder by weight. In some embodiments, the coating composition comprises about 5.6% by weight binder. In some embodiments, the composition does not comprise a binder. The composition may comprise more than one binder, wherein the total weight fraction of the binder in the composition is as described above.
[0043] The coating composition may also include one or more dispersants. Generally, the dispersant serves to prevent the inert material particles from settling prior to applying the coating composition to the inner surface 134 of the crystal base 118. Suitable dispersants generally do not add metallic impurities to the coating composition and burn out and decompose cleanly during thermal cycling. The combination of stabilizer and dispersant (described above) may be selected so that drying of the coating composition used to form the coating 140 is achieved with no or minimal cracking. In some embodiments, the dispersant is a non-aqueous polymeric dispersant, such as 20000 (available from Lubrizol Corp). The coating composition may include at least about 0.05% dispersant by weight, and in other embodiments, at least about 0.1%, at least about 0.5%, at least about 1%, or even at least about 5% dispersant by weight. In various other embodiments, the composition includes from about 0.05% to about 10% dispersant by weight, from about 0.05% to about 5%, or from about 0.5% to about 2.5% dispersant by weight. In some embodiments, the coating composition includes about 1.8% dispersant by weight. In some embodiments, the composition does not include a dispersant. The composition may include more than one dispersant, wherein the total amount of dispersant in the composition is as described above.
[0044] The coating composition may also include a stabilizer. Suitable stabilizers substantially do not add metallic impurities to the coating composition and burn and decompose cleanly during thermal cycling. The combination of stabilizer and dispersant (described above) may be selected so that drying of the coating composition used to form coating 140 is achieved with minimal or no cracking. For example, the stabilizer may be polyethylene glycol, such as Polyethylene glycol 400 (available from Dow Chemical Co.). The coating composition may contain at least about 0.5%, at least about 2%, at least about 5%, at least about 10%, or even at least about 15% stabilizer by weight. In various embodiments, the composition contains from about 0.5% to about 20% stabilizer, from about 0.5% to about 10%, from about 0.5% to about 8%, or from about 2% to about 8% stabilizer by weight. In some embodiments, the coating composition contains about 5.6% stabilizer by weight. In some embodiments, the composition does not contain a stabilizer. The composition may contain more than one stabilizer, wherein the total amount of stabilizer in the composition is as described above.
[0045] Non-limiting examples of techniques for applying a coating composition having inert material particles suspended in a liquid solution include brushing or aerosol spraying. In brushing application, the coating composition can be brushed onto the inner surface 134 of the crystal seat 118 using a brush (e.g., a foam brush). In aerosol spraying application, a pressurized spray gun can be used to apply the coating composition to the inner surface 134 of the crystal seat 118. Generally speaking, the coating composition has a lower liquid viscosity when applied by aerosol spraying than when applied by brushing techniques, enabling effective spraying of the coating composition. In this regard, the coating composition can include a smaller amount of inert material particles when applied by aerosol spraying than when applied by brushing. For example, a brushable coating composition can include more than 30% inert material particles by weight, such as from about 30% to about 50% inert material particles by weight, while a sprayable coating composition can include less than 30% inert material particles by weight, such as from about 5% to about 30% inert material particles by weight. Similarly, the coating composition can have a greater amount of medium when applied by aerosol spraying than when applied by brushing. For example, a brushable coating composition can include greater than 70% medium by weight, such as from about 70% to about 80% medium by weight, while a sprayable coating composition can include less than 60% medium by weight, such as from about 40% to about 60% medium.
[0046] The brushing and / or spraying application may be performed under a fume hood, suitably at atmospheric pressure and at a temperature below the flash point of the coating composition. Subsequently, the coating composition on the inner surface 134 of the crystal holder 118 is dried by air drying or heat treatment to remove the medium. The dispersant, binder and / or stabilizer in the coating composition may be included in an amount sufficient to help slow the surface evaporation of the medium so that an appropriate amount of the medium is removed from the bottom layer by evaporation. Otherwise, the surface of the outermost layer may peel too quickly before an appropriate amount of the medium has evaporated from the film mass, which may result in the formation of pinholes in the coating 140. In some embodiments, the coating composition may be applied and then dried multiple times to remove the medium to achieve the desired thickness.
[0047] Once the desired thickness has been achieved, the susceptor 118 may be heated to a temperature sufficient to decompose, vaporize, and / or expel the remaining liquid components (e.g., binder, dispersant, stabilizer, any remaining dielectric, etc.). Generally, heating may be achieved by heating the susceptor 118 having the coating composition applied to the inner surface 134 until the desired temperature is achieved. The binder, dispersant, stabilizer, remaining dielectric, etc. are removed to form the coating 140. These components may be removed until the coating 140 contains less than 5% residual carbon by weight, or less than about 3% or less than about 1% residual carbon by weight. In some embodiments, the susceptor 118 is heated to at least about 150° C., at least about 200° C., at least about 300° C., at least about 400° C., or even at least about 750° C. to remove any binder, stabilizer, dispersant, and remaining dielectric compounds. In various other embodiments, the susceptor 118 may be heated to from about 100° C. to 750° C., or from 400° C. to 750° C. The crystal susceptor 118 may be heated for at least about 1 hour, and in other embodiments, at least about 2 hours, at least about 3 hours, or from about 1 hour to about 5 hours. In some embodiments, the crystal susceptor 118 is heated to at least about 300° C. for at least about 2 hours. The atmospheric pressure may be a pressure (vacuum) from about 60 Torr (0.08 atm) to about 1 atmosphere or from about 150 Torr (0.20 atm) to about 1 atmosphere. In other embodiments, a pressure higher than atmospheric pressure is used, for example, a pressure of at least 1 atmosphere, at least 2 atmospheres, or even at least 5 atmospheres.
[0048] The susceptor 118 may be heated in the presence of an inert gas such as nitrogen, helium, or argon. Ambient air may also be used as the atmospheric pressure during heating but is not preferred because it may introduce oxygen into the coating 140. Furthermore, as will be appreciated by those skilled in the art, the materials of construction of the furnace as well as the gas flows may be controlled to avoid oxidation of the coating 140.
[0049] Thereby, the coating 140 comprises particulate material remaining from the coating composition (e.g., inert material particles and sintering additives described in further detail below). A sintering step may also be performed to densify and strengthen the coating 140. This may be performed in addition to and subsequent to the heating described above to remove the liquid component from the coating composition, or may be performed as a single step of removing the liquid component used to form the coating 140 and sintering the coating 140. In a particular embodiment, sintering is performed during the melting of the silicon charge to minimize the processing time. To achieve sintering, the crystal base 118 may be heated to a temperature from about 900° C. to about 1600° C. In some embodiments, the crystal base 118 is heated to a temperature of at least about 1000° C., at least about 1100° C., at least about 1400° C., or even at least about 1500° C. The coating 140 may be sintered at a temperature for a duration of from at least about 1 hour to several days. In some embodiments, the coating 140 is sintered for at least about 6 hours. The coating 140 may be sintered in the presence of an inert gas (e.g., nitrogen, helium, or argon). Atmospheric pressure can be a pressure (vacuum) from about 60 Torr (0.08 atm) to about 1 atmosphere or from about 150 Torr (0.20 atm) to about 1 atmosphere. In other embodiments, a pressure higher than atmospheric pressure is used, for example, a pressure of at least 1 atmosphere, at least 2 atmospheres, or even at least 5 atmospheres.
[0050] The coating 140 may also be formed by other application techniques, such as chemical vapor deposition or plasma spraying techniques. In a plasma spraying application, particles of an inert material and additional powder additives or particulate additives (e.g., sintering additives described in further detail below) are fed into a hot plasma jet (e.g., a DC plasma torch) through one or more powder feeders where the particles are mixed with a plasma gas (e.g., argon, helium, nitrogen, hydrogen, or a combination thereof). The particles have an appropriate size distribution (e.g., a size of about 5 μm to 100 μm) to facilitate proper mixing and movement through the plasma jet. The particles are accelerated at high speeds (e.g., 50 m / s-3000 m / s) and are rapidly heated to high temperatures (e.g., from about 2000° C. to about 3000° C.) and directed toward the inner surface 134 of the crystal holder 118. The softened or molten particles impact the inner surface 134 thereby depositing a coating 140 having a desired thickness between the crystal holder 118 and the crucible 104. Plasma spraying techniques may have several advantages over other deposition techniques (e.g., brushing or spraying applications). For example, plasma spraying may contribute to high efficiency in terms of throughput and ease of operation. Plasma spraying may also contribute to reduced processing time, since the need for a separate heating and / or sintering step to form the coating 140 may be eliminated. Furthermore, the processing conditions of the plasma spraying may be controlled to help adjust the coating properties. Furthermore, the coating 140 deposited by plasma spraying may suitably be a quasi-permanent staggered coating 140, thereby reducing the need to re-apply the coating 140 after several drawing processes using the crystal holder 118, which may be the case when the coating 140 is formed from a brushable coating composition or a sprayable coating composition.
[0051] When the coating 140 is formed, the particles contained in the coating 140 (e.g., inert material particles and additional particles, such as sintering additives described in further detail below) form a thin film that is interleaved between the graphite crystal base 118 and the quartz crucible 104. The interleaved coating 140 behaves as a sintered monolithic component and exhibits excellent chemical inertness between the graphite crystal base 118 and the quartz crucible 104. However, it has been observed that the interleaved coating 140 formed essentially of inert material particles (e.g., boron nitride) has minimal strength. Thereby, the inert material particles of the coating 140 have the possibility of breaking and separating from each other. For example, during the pulling process, loose inert material particles may be carried by the process gas flowing through the ingot puller 100 into the silicon melt 102. The inert material particles may then travel to the solid-molten interface of the growing ingot. Therefore, the ingot pulled from the melt 102 may be contaminated by the inert material particles, which negatively affects the resistivity of the ingot and the wafers cut from the ingot. For example, boron atoms or nitrogen atoms from loose boron nitride particles may be introduced into the melt 102 as undesirable dopants and may cause fluctuations in the resistivity of the ingot. Furthermore, the problem is exacerbated later in the pulling process as the loose powder continues to break off from the coating 140 over time. The loose powder accumulates in the area between the susceptor 118 and the crucible 104, which cannot be adequately cleaned when the pulling process is stopped, causing processing delays and increasing manufacturing time and cost. In order to make the coating 140 more functional and take advantage of the reduced reactivity between the carbon and silicon dioxide surfaces, it is desirable to provide an interlaced coating 140 with greater strength.
[0052] To this end, it has been discovered that sintering additives may be mixed with the inert material particles to help improve the durability of the coating 140 and help minimize the likelihood of the inert material particles breaking from the coating 140 and causing deleterious properties in an ingot grown using the puller 100 via cross contamination.
[0053] Thus, in an embodiment of the present disclosure, the coating 140 is formed of a mixture of inert material particles (e.g., boron nitride) and a sintering additive that promotes densification of the inert material particles in the coating 140, and generally improves the adhesion of the inert material particles to the inner surface 134 of the crystal base 118 and to each other. In particular, the sintering additive facilitates diffusion and bonding of the inert material by forming an interparticle liquid phase at a sintering temperature (e.g., from about 900° C. to about 1600° C.), thereby promoting densification of the inert material in the sintered coating 140. For example, the additive includes one or more of silicon oxide (silicon dioxide, SiO2), silicon carbide (SiC), boric acid (hydrogen borate, H3BO3), aluminum oxide (aluminum oxide, Al2O3), yttrium oxide (yttrium oxide, Y2O3), zirconium oxide (ZrO2), aluminum nitride (AlN), and lanthanum oxide (lanthanum oxide, (La2O3)).
[0054] The sintering additive is included in an amount suitable for achieving the target densification properties of the coating 140. In this regard, the amount of sintering additive included in the coating 140 can vary greatly, enabling the coating 140 to have a wide range of achievable strength properties. The target densification properties can be determined by the acceptable amount of cross-contamination of inert materials (e.g., boron nitride) in the silicon melt during the pulling process, which in turn can depend on the target resistivity of the ingots and wafers cut from those ingots.
[0055] In some examples, the ingot may have a high target resistivity. The high resistivity ingot may have a target resistivity of at least about 5000 ohm-cm, at least about 7500 ohm-cm, at least about 10,000 ohm-cm, or even at least about 100,000 ohm-cm. In these examples, cross contamination is appropriately minimized because undesired dopants introduced into the melt may have a relatively large effect on resistivity fluctuations. Therefore, in these examples, when sintering the coating 140, the sintering additive may be included in an amount sufficient to form at least a moderately adherent film with the inert material (e.g., boron nitride).
[0056] In some examples, the ingot may have a relatively low target resistivity. For example, the ingot may have a target resistivity of less than about 5000 ohm-cm, such as less than about 1000 ohm-cm, or even less than about 500 ohm-cm. In these examples, a relatively high amount of cross-contamination of inert materials (e.g., boron nitride) in the silicon melt may be acceptable. Therefore, in these examples, when sintering the coating 140, the sintering additive may be included in an amount sufficient to provide a loose lubrication system to densify the boron nitride.
[0057] Furthermore, the amount of sintering additive included in coating 140 must be such that coating 140 retains the inert properties provided by the inert material (eg, boron nitride).
[0058] Thus, the mass ratio of the sintering additive to the inert material (e.g., boron nitride) in the coating 140 can be from at least about 1:100 to as high as about 1:1. Typically, the sintering additive is not added in an amount that would exceed a mass ratio of about 1:1 of the sintering additive to the inert material. In some embodiments, the mass ratio of the sintering additive to the inert material is about 1:50, about 1:40, about 1:30, about 1:20, about 1:15, about 1:10, about 1:9, about 1:8, about 1:7, about 1:6, about 1:5, about 1:4, about 1:3, about 1:2, or about 1:1. As discussed above, the mass ratio can be selected to be any amount suitable for achieving the target densification properties of the coating 140. In a brush or spray application of the coating 140, the liquid coating composition can include at least about 0.01% by weight of the sintering additive up to about 30% by weight of the sintering additive. In various embodiments, the liquid coating composition applied by brushing or spraying may contain from about 1% to about 25% sintering additive by weight, from about 5% to about 20% by weight, or from about 10% to about 15% sintering additive by weight. In the plasma spray application of the coating 140, the sintering additive may be included in a mass ratio with the inert material particles as described above. Suitably, when the coating 140 is applied by plasma spraying, the mass ratio is from about 1:20 to about 1:1, from about 1:15 to about 1:1, or from about 1:10 to about 1:1 of sintering additive to inert material. In one example, when the coating 140 is applied by plasma spraying, the mass ratio is about 1:4 of sintering additive to inert material. When the coating 140 is applied by plasma spraying, the sintering additive may be included in an amount of at least about 0.01% to up to about 50% by weight relative to the weight of the inert material particles. In various embodiments, when the coating 140 is applied by plasma spraying, the sintering additive is included in an amount of from about 1% to about 50% by weight, from about 10% to about 40% by weight, or from about 20% to about 30% by weight relative to the weight of the inert material particles. In one example, when the coating 140 is applied by plasma spraying, the sintering additive is included in an amount of about 25% by weight relative to the weight of the inert material particles.
[0059] As discussed above, the sintering additive may be applied using a thermal coating process (e.g., plasma spraying) or a wet coating process (e.g., brushing or aerosol spraying of a liquid coating composition). Suitably, the sintering additive is included in an amount sufficient to enable particles of the inert material (e.g., boron nitride) to stick together to form a dense hardened coating 140. In this regard, the sintering additive is included to obtain a looser coating 140 than a coating 140 formed entirely or substantially entirely of an inert material (e.g., boron nitride). Thus, the sintering additive contributes to a lower likelihood of the coating 140 being cross-contaminated with particles of boron nitride that fall off and thus cross-contaminate the melt 102. In addition, the sintering additive is included in an amount suitable for avoiding degradation of the thermal durability and inert functionality of the coating 140 as described herein. That is, an excess of the sintering additive may result in a significant decrease in the thermal durability of the coating 140 compared to the thermal durability of a coating 140 formed entirely or substantially entirely of an inert material (e.g., boron nitride). In one example, the coating 140 is applied by plasma spraying, and is formed of a mixture of particles of boron nitride as an inert material, and a sintering additive is selected from silicon carbide (SiC), yttrium oxide (yttrium trioxide, Y2O3), aluminum nitride (AlN), lanthanum oxide (lanthanum trioxide (La2O3)), and a mixture of two or more of these materials, wherein the mass ratio of the sintering additive to boron nitride is about 1:4 (i.e., the sintering additive is included in an amount of about 25% by weight relative to the weight of boron nitride).
[0060] Sintering the coating 140 (or a coating composition used to form the coating 140) as described above, the coating comprising particles of an inert material (e.g., boron nitride) and a sintering additive to densify and strengthen the coating 140 may be performed. However, the sintering step is not limited to any particular sintering process, and the sintering step may be utilized whether the coating 140 is formed from a coating composition applied as a liquid solution or formed by plasma spraying. The sintering additive is able to appropriately function as described herein regardless of whether it is sintered in a vacuum, in an inert gas atmosphere, or in air. In the case of sintering in air, those sintering additives comprising oxides (e.g., silicon dioxide, boric acid, aluminum oxide, yttrium oxide, zirconium oxide, and lanthanum oxide) are appropriately used because the sintering additive is least likely to react in air during sintering. In addition, it should be understood that several mechanisms may contribute to sintering. For example, mechanisms such as the formation of a glass phase between grain boundaries may be initiated at as low as 900°C depending on the viscosity of the glass system, but more typically the mechanism will be initiated in the 1200°C to 1800°C range depending on the desired process duration at elevated temperatures. Another mechanism involves evaporation and condensation of sintering additives, where transport and subsequent densification occurs by evaporation of the sintering additives, where the sintering additives are transported by vapor, then the components are condensed in a vapor phase condensation mode with subsequent densification and strength development. Another mechanism is solid diffusion within the sintering additives, also with strength development. At a given temperature or pressure, the extent of strength or physical property development will also depend on duration as a factor as well.
[0061] refer to Figure 3A and 3B , showing example distributions 300A and 300B of a mixture of sintering additives and inert material particles (eg, boron nitride). Specifically, these show two example methods for obtaining a mixture of inert material particles and sintering additives to help improve the strength of the sintered coating 140.
[0062] exist Figure 3A In the embodiment, the separated particulate mixture 300A includes sintering additive particles 302A directly mixed with inert material particles 304A. The separated particulate mixture 300A can be sent to a coating 140 ( Figure 2 ) of the plasma spray particles. Additionally, the separated particulate mixture 300A may be added to the coating composition as separate particles 304A of an inert material and particles 302A of a sintering additive, whereby the particles 302A and 304A are suspended in a liquid solution comprising, for example, a medium, a dispersant, a binder, a stabilizer, and the like.
[0063] exist Figure 3B In the embodiment, the coated particulate mixture 300B includes inert material particles 304B coated with a sintering additive 302B. To form the coated particulate mixture 300B, the sintering additive 302B is added to an aqueous solution, and the inert material particles 304B are washed with the solution containing the sintering additive 302B. After washing, the inert material particles 304B are coated, and the slurry is dried to remove the aqueous medium (e.g., water), thereby producing the coated particulate mixture 300B. The coated particulate mixture 300B can then be sent to a plasma spraying machine for forming the coating 140 ( Figure 2 ) of the coated particulate mixture 300B. In addition, the coated particulate mixture 300B may be added to the coating composition, whereby the coated particulate mixture 300B is suspended in a liquid solution containing, for example, a medium, a dispersant, a binder, a stabilizer, and the like.
[0064] According to the present disclosure, both methods can contribute to a mixture of inert material particles and sintering additives having a wider range of functionality. The method selected depends on the quality of the sintering additives to be used to obtain sufficient sintered strength. Thus, the method selected will depend on the target densification properties of the coating 140, the target inertness of the coating 140, and / or the tolerance level for cross contamination. Coated particulate mixture 300B ( Figure 3B One advantage of the mixture 300B (shown in FIG. 1 ) is that the mixture 300B provides a higher point contact of the sintering additive 302B with another grain that will be in contact with the sintering additive 302B. Therefore, to obtain the mechanical strength of the coating 140, less sintering additive 302B may be required. However, in order to obtain such a distribution and control the particle size of the inert material particles 304B coated with the sintering additive 302B to obtain the desired mechanical properties of the coating 140, the upper front processing of the particulate mixture 300B itself will require some additional process steps. In contrast, the separated particulate mixture 300A ( Figure 3A ) is more of a mechanical mixture that uses an incident particle size distribution of the sintering additive particles 302A and the inert material particles 304A. Particle-to-particle contact (where the sintering additive particles 302A contact each other across the grains) has a lower incidence, and therefore a higher weight loading of the sintering additive particles 302A may be required. The actual morphology and distribution of the particles may be selected based on factors desired in the final coating 140, such as desired thin film coating density, scratch resistance, durability, etc.
[0065] Advantages of using the disclosed coatings include reducing or preventing the formation of gaseous products, such as carbon (C) from the graphite crystal base and silicon dioxide (SiO2) from the quartz crucible. (s) +SiO 2(s) →CO (g) +SiO(g) ) produced by the inert materials used to form the coating. Additional advantages include promoting densification of the inert materials used to form the coating, thereby increasing the strength of the coating and reducing cross contamination of the silicon melt with the inert coating material. Furthermore, the coating utilizes materials that facilitate a wider range of functionality that can be tailored by the target specifications of the ingot grown by the pulling process. Furthermore, the coating can be suitably applied as a quasi-permanent film, facilitating reducing the frequency with which the coating needs to be applied between drawing processes.
[0066] As used herein, the terms "approximately," "substantially," "essentially," and "about," when used in conjunction with ranges of size, concentration, temperature, or other physical or chemical properties or characteristics, are meant to cover variations that may exist in the upper and / or lower limits of the range of the property or characteristic, including variations caused, for example, by rounding, measurement methodology, or other statistical variations.
[0067] When introducing elements of the present disclosure or embodiments thereof, the articles "a," "an," "the," and "said" are intended to mean that there are one or more of the elements. The terms "comprising," "including," and "having" are intended to be inclusive and mean that there may be additional elements in addition to the listed elements. The use of terms indicating a particular orientation (e.g., "top," "bottom," "side," etc.) is for convenience of description and does not require any particular orientation of the items described.
[0068] As various changes could be made in the above constructions and methods without departing from the scope of the disclosure, it is intended that all matter contained in the above description and shown in the accompanying drawings shall be interpreted as illustrative and not in a limiting sense.
Claims
1. A method for producing a single crystal silicon ingot from a silicon melt, comprising: providing a graphite crystal seat having an inner surface defining a cavity; depositing a coating onto the inner surface of the crystal seat, the coating comprising boron nitride and a sintering additive, wherein the sintering additive promotes densification of the boron nitride; positioning a quartz crucible in the cavity of the crystal base, the crucible having an outer surface contacting the coating; adding polycrystalline silicon to the crucible; heating the polycrystalline silicon to form a silicon melt in the crucible; and A single crystal silicon ingot is pulled out from the silicon melt.
2. The method of claim 1, wherein depositing the coating comprises plasma spraying the boron nitride and the sintering additive onto the inner surface of the crystal susceptor.
3. The method according to claim 1 or claim 2, wherein the mass ratio of the sintering additive to the boron nitride in the coating is from 1:20 to 1:
1.
4. The method of claim 1 , wherein depositing the coating comprises applying a coating composition to the inner surface of the crystal base, the coating composition comprising the boron nitride, the sintering additive, an organic medium, and optionally one or more of a stabilizer, a binder, and a dispersant.
5. The method of claim 4, further comprising removing the organic medium and, if present, the one or more of the stabilizer, the binder, and the dispersant from the coating composition applied to the inner surface of the crystal base to thereby form the coating.
6. The method of claim 5, further comprising sintering the coating during and / or after removing the organic medium and, when present, the one or more of the stabilizer, the binder, and the dispersant.
7. The method of any one of claims 4 to 6, wherein the coating composition comprises from 0.1% to 50% by weight of the boron nitride.
8. The method according to any one of claims 4 to 7, wherein the mass ratio of the sintering additive to the boron nitride in the coating is from 1:100 to 1:
1.
9. The method of any one of claims 1 to 8, wherein the sintering additive comprises silicon dioxide, silicon carbide, boric acid, aluminum oxide, yttrium oxide, zirconium oxide, aluminum nitride, lanthanum oxide, or a combination thereof.
10. A graphite crystal susceptor for supporting a quartz crucible during a crystal growth process, the crystal susceptor comprising: a body having an inner surface defining a cavity having a size and shape complementary to an outer size and shape of the crucible; as well as A coating is deposited onto the inner surface, the coating comprising boron nitride and a sintering additive, wherein the sintering additive is configured to promote densification of the boron nitride. 11 . The crystal seat according to claim 10 , wherein the mass ratio of the sintering additive to the boron nitride in the coating is from 1:100 to 1:
1. 12 . The crystal seat according to claim 10 , wherein a mass ratio of the sintering additive to the boron nitride in the coating is from 1:20 to 1:
1.
13. The crystal seat of any one of claims 10 to 12, wherein the coating is deposited onto the inner surface of the crystal seat by plasma spraying the boron nitride and the sintering additive.
14. The crystal seat according to any one of claims 10 to 13, wherein the mass ratio of the sintering additive to the boron nitride in the coating is from 1:5 to 1:
1.
15. The crystal pedestal of any one of claims 10 to 12, wherein the coating is deposited by applying a coating composition comprising the boron nitride, the sintering additive, and an organic medium to the inner surface of the crystal pedestal and subsequently removing the medium.
16. The crystal seat of any one of claims 10 to 15, wherein the sintering additive comprises silicon dioxide, silicon carbide, boric acid, aluminum oxide, yttrium oxide, zirconium oxide, aluminum nitride, lanthanum oxide, or a combination thereof.
17. A method for forming a coating between an inner surface of a graphite crystal seat and an outer surface of a quartz crucible, the method comprising: providing a particle mixture of boron nitride and a sintering additive; depositing the particulate mixture of the boron nitride and the sintering additive onto the inner surface of the crystal base; and The deposited particulate mixture is sintered to thereby form the coating, wherein sintering the deposited particulate mixture includes using the sintering additive to promote densification of the boron nitride.
18. The method of claim 17, wherein sintering the deposited particulate mixture occurs during and / or after depositing the particulate mixture.
19. The method of claim 17 or claim 18, wherein the sintering additive comprises silicon dioxide, silicon carbide, boric acid, aluminum oxide, yttrium oxide, zirconium oxide, aluminum nitride, lanthanum oxide, or a combination thereof.
20. The method of any one of claims 17-19, wherein providing the particulate mixture comprises mixing separate particles of the boron nitride and the sintering additive to form a separate particulate mixture.
21. The method of claim 20, wherein depositing the particle mixture comprises plasma spraying the separated particle mixture onto the inner surface of the crystal base.
22. The method of claim 20, further comprising: providing a coating composition comprising the separated mixture of microparticles suspended in an organic medium and optionally one or more of a stabilizer, a binder, and a dispersant; depositing the separated particle mixture by applying the coating composition to the inner surface of the crystal base; and During and / or after sintering the deposited separated particle mixture, the medium and the optional one or more of the stabilizer, the binder and the dispersant are removed.
23. The method of any one of claims 17-19, wherein providing the particulate mixture comprises providing a coated particulate mixture comprising the boron nitride particles coated with the sintering additive.
24. The method of claim 23, wherein depositing the particle mixture comprises plasma spraying the coated particle mixture onto the inner surface of the crystal base.
25. The method of claim 23, further comprising: providing a coating composition comprising the coated microparticle mixture suspended in an organic medium and optionally one or more of a stabilizer, a binder, and a dispersant; depositing the coated particulate mixture by applying the coating composition to the inner surface of the crystal base; and During and / or after sintering of the deposited coated particulate mixture, the medium and the optional one or more of the stabilizer, the binder, and the dispersant are removed.
Citation Information
Cited By
Crucible and manufacturing method thereof
CN120758964A